2021
DOI: 10.3389/fphar.2021.634087
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Degradable Starch Microspheres Transcatheter Arterial Chemoembolization (DSM-TACE) in the Downstaging of Intermediate-Stage Hepatocellular Carcinoma (HCC) in Patients With a Child-Pugh Score of 8-9

Abstract: According to the EASL Guidelines for the management of hepatocellular carcinoma, transcatheter arterial chemoembolization is the first-line treatment recommended for intermediate-stage HCC. Furthermore, it is widely accepted that patients beyond the Milan criteria can be considered for a liver transplant after successful downstaging to within the Milan criteria. Response to downstaging treatments significantly influences not just drop-outs, but also the rate of post-transplantation tumor recurrences. TACE with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…According to both the CTCAE and the CIRSE classification systems, patients experienced a global rate of adverse events after chemoembolization that is comparable to previous data on cTACE, DSM-TACE, or DEB-TACE, performed with conventional femoral or radial accesses [19,20,39,[54][55][56], and on other procedures in the endovascular fields [57][58][59]. Finally, in our investigation, we did not observe significant differences in terms of safety endpoints between the group undergoing DEB-TACE with femoral access and the group undergoing DEB-TACE with distal radial access.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…According to both the CTCAE and the CIRSE classification systems, patients experienced a global rate of adverse events after chemoembolization that is comparable to previous data on cTACE, DSM-TACE, or DEB-TACE, performed with conventional femoral or radial accesses [19,20,39,[54][55][56], and on other procedures in the endovascular fields [57][58][59]. Finally, in our investigation, we did not observe significant differences in terms of safety endpoints between the group undergoing DEB-TACE with femoral access and the group undergoing DEB-TACE with distal radial access.…”
Section: Discussionsupporting
confidence: 77%
“…A 5-Fr 125 cm hydrophilic-angiographic catheter (Cobra, Simmons, Multipurpose; Radifocus Glidecath; Terumo Corp, Tokyo, Japan) with a hydrophilic guide wire (Radifo-cus™ Guide Wire M Standard Type 0.035" 260 Cm Angled; Terumo Corp, Tokyo, Japan) was used for the selective celiac trunk catheterization and the cannulation of the common hepatic artery. Subsequently, the remaining endovascular procedural steps were performed as previously described [19].Whenever possible, a superselective approach (via tumorfeeding vessels) was obtained using the above microcatheter; alternatively, a pattern of segmental, lobar, or whole-liver (proper hepatic artery) chemoembolization was followed. LifePearl microspheres 200 ± 50 µm (Terumo Corp, Tokyo, Japan) were loaded with Doxorubicin, at a dose of 75 mg/m 2 body surface area, and non-ionic iodinated contrast media, according to the manufacturer's instructions for use.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…DSM-TACE using DSM, which is decomposed by blood amylase and has a short arterial embolization period in the body of up to 50 min, has been reported in cases of portal vein thrombosis [ 109 , 110 , 111 ]. Minici et al [ 112 , 113 ] reported that DSM-TACE could be used safely and effectively as bridging or downstaging for patients with poor hepatic reserve (Child-Pugh score 8–9 points). Radioembolization using Yttrium-90 is reported to treat target lesions more completely for early intermediate stage HCC than conventional TACE [ 114 ].…”
Section: Variations Of Pre-transplant Locoregional Therapiesmentioning
confidence: 99%
“…Minici et al [26] studied 50 of their own patients who received a total of 142 treatment procedures from 2015 to 2020. Treatment consisted of a mixture of DSM, non-ionic contrast medium and doxorubicin (50 mg) -but without lipiodol.…”
Section: Whichmentioning
confidence: 99%